Voltage imbalance compensation using synchronous compensator with multivariable filter in microgrids - Alireza Mohammadi Amidi; Pooya Parvizi; Milad Jalilian; Hana Parvizi (Majlesi Journal of Electrical Engineering, 2024)
Unbalanced voltage is a prevalent issue in power networks that can have significant adverse effects. Voltage unbalance arises when the three-phase voltages in the power system differ in magnitude or phase angle, leading to waveform distortion. This imbalance can increase energy losses, thereby elevating costs for energy consumers. Additionally, it can negatively impact the power factor, which measures the efficiency of power usage in the system. To improve power quality and mitigate the detrimental effects, this paper  proposes an innovative control strategy using a Static Synchronous Compensator (STATCOM) based on the multivariable filter (MVF) method within a utility-connected microgrid. The MVF configuration effectively separates the positive and negative components, which are then utilized in control loops. First, the voltage control loop builds the references for current control loop. Then, the current control unit sends the appropriate commands to the STATCOM in order compensate the votage amplitude. The primary advantage of the proposed strategy is its precision in reference tracking and ease of implementation. The MVF-based STATCOM can compensate for voltage imbalances by injecting reactive power and regulating the DC-link voltage. The results demonstrate that the proposed control structure effectively eliminates negative components and enhances the voltage profile of the studied microgrid.